Seals of the 11th-9th century BCE from Israel made of oil shale - Amorai-Stark, S.; Rosenfeld, A.; Minster, T. (Liber Annuus, 2005)
Abstract A group of conoid and scaraboid seals from the Judea and Samaria regions dating from the 11th-9th century BCE was examined stylistically as well as geochemically. The group includes seven rare large seals, which are recorded here for the first time, and three common smaller ones presented for comparison. All exhibit cultic scenes, hunting scenes and zoomorphic motifs. The majority were produced from a local black, high bituminous chalk. However, the seals yield carbon contents higher than the natural stones, which led us to the assumption that oil was added deliberately. Our examinations have indicated that immersion in oil has technical advantages facilitating the engraving process. In addition, the culticreligious importance of anointing objects, as well as persons and places, during the Early Iron Age is discussed, raising the possibility that the seals also could have a cultic-religious significance.